The Role of Teacher Skills in Create Environment Learning Innovative in Social Studies Lessons for Grade 9 at Teladan Foundation Middle School Binjai - Citra Aulia; Risbue Siregar; Kerin Sisca Octaviani Luahambowo; Dumayanti Situmorang (Jurnal Multidisiplin Sahombu, 2024)
This research discusses the importance of teacher skills in creating an innovative learning environment in grade 9 social studies subjects at Yayasan Teladan Junior High School in Binjai . The method used was interviews with social studies teachers to explore the strategies and approaches applied during the learning process. The results showed that teachers' skills play an important role in creating a conducive classroom atmosphere, through the application of clear rules, interesting learning activities, and the use of technology. Despite facing obstacles such as students' preference for traditional methods, teachers' efforts to increase students' engagement through discussion and group work proved effective. This study concludes that teacher skills have a significant contribution to learning innovation in the 21st century era .